2003
DOI: 10.1021/jp035632x
|View full text |Cite
|
Sign up to set email alerts
|

Spin States of C603-and C120On-(n= 2, 3, 4) Anions Using Electron Spin Transient Nutation Spectroscopy

Abstract: Electron spin transient nutation (ESTN) experiments show that the spin multiplicity of the ground state of C 60 3-in frozen solution is a doublet with S ) 1 / 2 . In purified samples, there is no evidence for excited states or other species with higher multiplicity. In the anions of C 120 O n-(n ) 2, 3, 4), where the CW EPR experiments have shown that a mixture of species is present, ESTN experiments confirm that a doublet with S ) 1 / 2 is associated with the 3-anion and triplets with S ) 1 are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…However, there was a controversy 27 on whether the low-spin/high-spin gap is very small (below one wavenumber 28 ) or rather of the order of 600 wavenumbers 29 . Recently, this problem was carefully reconsidered and it was shown that activated behaviors of C N − 60 which were observed so far and used to determine the gap are in fact due to C 120 O impurities 30,31 . However, the work clearly reconfirms that iso-lated C N − 60 ions (N = 2, 3) are in the low-spin state.…”
Section: Results For C60mentioning
confidence: 99%
“…However, there was a controversy 27 on whether the low-spin/high-spin gap is very small (below one wavenumber 28 ) or rather of the order of 600 wavenumbers 29 . Recently, this problem was carefully reconsidered and it was shown that activated behaviors of C N − 60 which were observed so far and used to determine the gap are in fact due to C 120 O impurities 30,31 . However, the work clearly reconfirms that iso-lated C N − 60 ions (N = 2, 3) are in the low-spin state.…”
Section: Results For C60mentioning
confidence: 99%
“…EPR spectra indicated a triplet state, while a study using electron spin transient nutation spectroscopy suggested an extremely low separation of only 5 cm −1 between the singlet and triplet states for C 120 O 2− in solution. 16,17 Our calculation predicted a small ͑2 kJ/ mol͒ spin excitation for the isolated dianion. However, it should be noted that for molecular systems of such large size even much more demanding computational methods are unlikely to provide a level of accuracy comparable to the true gap.…”
Section: A Spin Coupling: Is C 120 O 2− Singlet or Triplet?mentioning
confidence: 73%
“…Anions of C 120 O ͑C 120 O n− ͒ are common impurities in solutions of C 60 n− and have been studied by electron paramagnetic resonance ͑EPR͒ spectroscopy. 16,17 The isolated C 120 O 2− dianion is an interesting model system to study spin couplings and electron correlations. There are several important questions: How are the two excess electrons distributed in the molecule?…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a controversy 27 on whether the low-spin/high-spin gap is very small (below one wavenumber 28 ) or rather of the order of 600 wavenumbers 29 . Recently, this problem was carefully reconsidered and it was shown that activated behaviors of C N − 60 which were observed so far and used to determine the gap are in fact due to C 120 O impurities 30,31 . However, the work clearly reconfirms that iso-lated C N − 60 ions (N = 2, 3) are in the low-spin state.…”
Section: Results For C60mentioning
confidence: 99%